RENCANA PRODUKSI OLAHAN KOPI DI PERUSAHAAN DAERAH PERKEBUNAN (PDP) KAHYANGAN JEMBER MENGGUNAKAN METODE FUZZY TSUKAMOTO - Yuli Wibowo; Yeyen Retno Maulida; Bambang Herry Purnomo (AGROINTEK, 2019)
PDP Kahyangan Jember is a regional company owned by the Government of Jember Regency that has agroindustry ground coffee and roasted coffee. The problem is that there was a mismatch between the company's production plan and the number of consumer demand that cause the stock. The impact is that production costs will increase because of the cost of storing and the production process becomes disrupted due to the location of the product storage warehouse in place together with the production space. The purpose of this research is to evaluate and to make a production plan model at PDP Kahyangan Jember. The method used is fuzzy Tsukamoto with input variables in the form of consumer demand and stock. The results showed that the prediction of the quantity of ground coffee and roasted coffee in the past year (July 2017-June 2018) resulted in a MAPE value of 16%. The MAPE value obtained is "good" because it was in between 10-20%. The results of the fuzzy Tsukamoto model simulation for future production plans are done by predicting the number of requests in advance using the DES Brown method and the stock using the SES method. The forecasting results for the number of requests for coffee were 3,304 kg, 3,261 kg, 3,219 kg, 3,176 kg, 3,134 kg, and 3,091 kg. While the stock forecasting results are 283 kg, 205 kg, 173 kg, 151 kg, 140 kg, and 134 kg. Therefore, the production plan of coffee processed using fuzzy Tsukamoto for July - December 2018 are 4144 kg, 4136 kg, 4130 kg, 4121 kg, 4110 kg and 4095 kg respectively.